1998
DOI: 10.1037/0096-3445.127.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Aging and source monitoring: Cognitive processes and neuropsychological correlates.

Abstract: This study shows that relative to younger adults, older adults are more adversely influenced by similar items when judging a memory's source, and the phenomenal features of their correctly and incorrectly attributed memories have greater overlap. The authors argue in accordance with the source monitoring framework that this age-related impairment in source accuracy is related to processes involved in binding features into complex memories and those involved in accessing and evaluating contextual features of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
229
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(253 citation statements)
references
References 138 publications
17
229
2
4
Order By: Relevance
“…Older adults were more likely to pick an innocent foil than were younger adults. Currently the most likely explanation for this is age related deficits in context recollection and source memory (Chalfonte and Johnson, 1996;Henkel et al, 1998;Jennings and Jacoby, 1997). These processes are critical in an eyewitness context where when someone makes a positive identification they are saying they have previously seen the face in a specific context.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults were more likely to pick an innocent foil than were younger adults. Currently the most likely explanation for this is age related deficits in context recollection and source memory (Chalfonte and Johnson, 1996;Henkel et al, 1998;Jennings and Jacoby, 1997). These processes are critical in an eyewitness context where when someone makes a positive identification they are saying they have previously seen the face in a specific context.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have tested diverse contexts: the modality, visual or auditory, in which stimuli were previously presented (McIntyre and Craik, 1987), who presented the information (Schacter et al, 1991), whether the stimuli were previously perceived or imagined (Henkel et al, 1998), the voice that presented the information (Glisky et al, 2001), if the participant asked for, answered or listened to certain information (Brown et al, 1995), or in which room, color or set of stimuli were the items previously presented (Spencer and Raz, 1994). All of these experiments confirmed that older adults perform poorer in the source-memory task than younger adults.…”
Section: Source-memory Decline Across Lifespanmentioning
confidence: 99%
“…Degradation in the frontal lobes occurs with aging (Anderson & Craik, 2000;West, 1996), and the frontal lobes are particularly susceptible to volumetric reduction as a person ages (Buckner, 2004;Raz, 2000). Because the frontal lobes are implicated in processes such as source monitoring (Henkel, Johnson, & De Leonardis, 1998), declines in frontal lobe functioning might reduce an older adult's ability to avoid false memories. A corollary of this idea is that older adults who do not show age-related frontal deficits may exhibit memory performance similar to that of younger adults.…”
mentioning
confidence: 99%